PENGUSAHA PEREMPUAN SEBAGAI AGEN PERUBAHAN: STUDI KOMPARASI PERAN PEREMPUAN SEBAGAI WIRAUSAHA SOSIAL DI NEGARA BERKEMBANG - Biru, Rembulan Catra Banyu; Fahmi, Rahmat; Sulistiono, Eko (NOKEN : Jurnal Pengelolaan Pendidikan, 2021)
This research is motivated by the social problems faced by several developing countries. The contribution of women entrepreneurs is very important. Women's entrepreneurship can be said to be an agent of change because it plays an important role in socio-economic development and in poverty alleviation. The purpose of this study is to compare the role of women as social entrepreneurs in developing countries. The object of this research is women entrepreneurs from developing countries, namely Indonesia, Malaysia, Sub-Saharan Africa, India, and Cameroon. Content analysis is a method used to analyze data. The results show that women entrepreneurs in developing countries have made a significant contribution to their society by adopting business models to offer creative solutions to social problems at hand. In other words, women entrepreneurs have become agents of change in society. The new findings show that in the context of social entrepreneurship, women are more suitable to lead social enterprises.Keywords: women entrepreneurs; change agents; social entrepreneurs; social enterprises